Climate Change Impact on Natural Hazards in Kabul City - Kabirzad, Shabir Ahmad; Ahmadzai, Mujib Rahman (Journal of Natural Sciences – Kabul University, 2020)
Afghanistan is a developing country suffering from the effects of climate change. Kabul, the capital city, needs an assessment to evaluate the climatic impact in recent years due to heavy rainfall and flash floods. This study conducted an assessment in districts 6, 8, 13, and 16 of Kabul city and found that the lack of water management infrastructure, such as drainage canals, increases the risk of heavy rainfall and flash flooding within the city. During the survey, respondents reported suffering from flash floods due to heavy rainfall and poor drainage capacity. To address groundwater depletion and manage the climatic impacts, the study proposed solutions for surface and groundwater management, which will alleviate the socioeconomic impact of drought. Indeed, climate change will continue to affect the social and economic dimensions of citizens in the future.